Protein Compositions Changes of Circulating Microparticles in Patients With Valvular Heart Disease Subjected to Cardiac Surgery Contribute to Systemic Inflammatory Response and Disorder of Coagulation. Issue 5 (November 2019) - Jian, Yu-Peng; Yuan, Hao-Xiang; Hu, Kun-Hua; Chen, Chao; Li, Yu-Quan; Li, Yan; Yang, Tian-Xin; Ou, Zhi-Jun; Ou, Jing-Song
Abstract : ABSTRACT: We recently demonstrated that circulating microparticles (MPs) from patients with valvular heart diseases (VHD) subjected to cardiac surgery impaired endothelial function and vasodilation. However, it is unknown whether or not the protein composition of these circulating MPs actually changes in response to the disease and the surgery. Circulating MPs were isolated from age-matched control subjects (n = 50) and patients (n = 50) with VHD before and 72 h after cardiac surgery. Proteomics study was performed by liquid chromatography and mass spectrometry combined with isobaric tags for relative and absolute quantification technique. The differential proteins were identified by ProteinPilot, some of which were validated by Western blotting. Bio-informatic analysis of differential proteins was carried out. A total of 849 proteins were identified and 453 proteins were found in all three groups. Meanwhile, 165, 39, and 80 proteins were unique in the control, pre-operation, and postoperation groups respectively. The unique proteins were different in localization, molecular function, and biological process. The pro-inflammatory proteins were increased in VHD patients and more so postoperatively. Proteins related to coagulation were dramatically changed before and after surgery. The protein composition of circulating MPs was changed in patients with VHD undergoing cardiac surgery, which may lead to activation of the systemic inflammatory response and disorders of coagulation. Abstract : Supplemental Digital Content is available in the text